Spatial Contrast Sensitivity to Polarization and Luminance in Octopus - Nahmad-Rohen, Luis; Vorobyev, Misha (Frontiers in Physiology, 2020)
While color vision is achieved by comparison of signals of photoreceptors tuned to different parts of light spectra, polarization vision is achieved by comparison of signals of photoreceptors tuned to different orientations of the electric field component of visible light. Therefore, it has been suggested that polarization vision is similar to color vision. In most animals that have color vision, the shape of luminance contrast sensitivity curve differs from the shape of chromatic contrast sensitivity curve. While luminance contrast sensitivity typically decreases at low spatial frequency due to lateral inhibition, chromatic contrast sensitivity generally remains high at low spatial frequency. To find out if the processing of polarization signals is similar to the processing of chromatic signals, we measured the polarization and luminance contrast sensitivity dependence in a color-blind animal with well-developed polarization vision, Octopus tetricus. We demonstrate that, in Octopus tetricus, both luminance and polarization contrast sensitivity decrease at low spatial frequency and peak at the same spatial frequency (0.3 cpd). These results suggest that, in octopus, polarization and luminance signals are processed via similar pathways.